AB0449 Baseline Procalcitonin (PCT) Level as A Predictive Marker for Clinical Remission (DAS28-ESR, CDAI) at 52 Weeks in Biologic NaÏVe Rheumatoid Arthritis (RA) Patients Treated by TOCILIZUMAB (TCZ); A Single Center Retrospective Study. (10th June 2014) - Tsuji, S.; Yura, A.; Katayama, M.; Watanabe, A.; Teshigawara, S.; Yoshimura, M.; Tanaka, E.K.; Harada, Y.; Kagawa, K.; Katada, Y.; Matsushita, M.; Ohshima, S.; et al.
Abstract : Background: The goal in treating RA has changed from clinical remission to structural remission with the increased use of biological agents (Bio) which target the pro-inflammatory cytokines interleukin (IL)-6 and tumor necrosis factor (TNF)-α. PCT, a useful marker of infection, has been shown to increase in mRNA expression in peripheral blood mononuclear cells by stimulated by pro-inflammatory cytokine, IL-6 or TNF-α. Objectives: This study investigates whether the levels of following parameters (PCT, modified HAQ (mHAQ), MMP-3, RF, ESR, CRP and ACPA) at baseline (BL) of TCZ treatment can be used to predict clinical remission (DAS28-ESR, CDAI) at 52 weeks after the start of TCZ treatment. Methods: Bio naïve RA patients who can be observed at Week 52 were analyzed in this study. PCT (n=34), mHAQ (n=48), matrix metalloproteinase (MMP)-3 (n=54), RF (n=54), ESR (n=53), CRP (n=56) and ACPA (n=52) were assessed at BL. The patients were divided into 2 groups, based on DAS28-ESR remission (DAS28-ESR<2.6) at Week 52. For each variable where there was a significant difference between the remission and non-remission groups, receiver operating characteristic (ROC) analysis was performed and cut-off values (COV) were found. For each of those variables, 2 groups were formed by dividing the Bio naïve RA at the COV: the under COV (U) group and over COV (O) group, and the Week 52 clinical remission (DAS28-ESR, CDAI) rate in each group were analyzed. Results: The variables with a significant difference between the remission and non-remission groups were PCT (p=0.001), mHAQ (p=0.014), RF (p=0.003), ESR (p=0.001) and CRP (p=0.041). The COVs were 0.027 ng/ml for PCT, 100U/ml for RF, 0.38 for mHAQ, 18 mm/hr for ESR, 1.96 mg/dl for CRP. For each variable, the DAS28-ESR remission rate in U group (PCT: 100%, mHAQ: 70.8%, RF: 77.8%, ESR: 87.5% and CRP: 64.3%) was significantly higher than in O group. Additionally, the CDAI remission rate in U group (PCT: 50.0% (p=0.040) and RF: 32.1% (p=0.026)) was significantly higher than in O group, but not others. For PCT at BL, DAS28-ESR or CDAI were no different between the U group and O group and no correlation with DAS28-ESR or CDAI were observed. BL DAS28-ESR was significantly lower in U groups for all other variables. Furthermore, BL PCT had correlation with DAS28-ESR and CDAI at Week 52. Conclusions: BL PCT level is a useful predictive marker for clinical remission (DAS28-ESR, CDAI) at week 52 in Bio naïve RA treated by TCZ. Moreover, unlike other variables, it is not affected by the BL disease activity level. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2437